Infrastructure Development and Ape Conservation - Foundation, Arcus (Life Sciences, 2018)
This third volume analyses the impact of large scale infrastructure development on ape conservation and the opportunities for reconciling social and economic development with the conservation of biodiversity. It includes contributions and case studies from a wide range of practitioners, academics, experts and environmental/campaign organisations. This title is also available as Open Access via Cambridge Core.